2013
DOI: 10.3390/ijms140510090
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Induces CXCL1 Chemokine Release via JNK and PI-3K-Dependent Pathways in Human Lung Carcinoma Epithelial Cells

Abstract: Lung cancer cells express different chemokines and chemokine receptors that modulate leukocyte infiltration within tumor microenvironment. In this study we screened several mediators/growth factors on CXCL1 release in human carcinoma epithelial cells. Of the tested mediators, VEGF was found to have a robust increase in causing CXCL1 release. VEGF stimulated CXCL1 release and mRNA expression in a time- and concentration-dependent manner. The release was inhibited by the VEGF receptor antagonists and the JNK, PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…6b), suggesting that lack of presenilins affects TNF␣-mediated CXCL1 chemokine production. Interestingly, and consistent with our reported defect in JNK MAPK activation in PS DKO MEFs, it has been reported that CXCL1 production is dependent upon TNF␣-stimulated JNK MAPK activation (72)(73)(74). To further validate this observation, we used wild type and the partial knock-out Psen1 ϩ/Ϫ / Psen2 Ϫ/Ϫ murine model, which have the maximum reduction in presenilin expression that is compatible with viability.…”
Section: Presenilin Deficiency Is Associated With Enhanced Formation mentioning
confidence: 67%
“…6b), suggesting that lack of presenilins affects TNF␣-mediated CXCL1 chemokine production. Interestingly, and consistent with our reported defect in JNK MAPK activation in PS DKO MEFs, it has been reported that CXCL1 production is dependent upon TNF␣-stimulated JNK MAPK activation (72)(73)(74). To further validate this observation, we used wild type and the partial knock-out Psen1 ϩ/Ϫ / Psen2 Ϫ/Ϫ murine model, which have the maximum reduction in presenilin expression that is compatible with viability.…”
Section: Presenilin Deficiency Is Associated With Enhanced Formation mentioning
confidence: 67%
“…There is a close association between smoking and lung carcinoma; in addition, atmospheric pollution and automobile exhaust fumes are also lung cancer risk factors. Furthermore, chronic bronchitis, pulmonary heart disease, pulmonary fibrosis, pulmonary tuberculosis and pneumoconiosis are associated with the incidence of lung cancer (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…We previously found that TNF-α, VEGF, lipopolysaccharide and thrombin treatment can lead to CXCL1 induction, and we also elucidated the possible mechanism of action of VEGF in causing CXCL1 release by A549 lung epithelial carcinoma cells [19]. Given that TNF-α is a potent proinflammatory cytokine and has been shown to be expressed in the lung tumor microenvironment [5], the effects of TNF-α on CXCL1 release in human A549 lung carcinoma epithelial cells were investigated in the present study.…”
Section: Introductionmentioning
confidence: 99%